2022
DOI: 10.1186/s13098-022-00895-w
|View full text |Cite
|
Sign up to set email alerts
|

The association between advanced glycation end products (AGEs) and ABC (hemoglobin A1C, blood pressure, and low-density lipoprotein cholesterol) control parameters among patients with type 2 diabetes mellitus

Abstract: Background Diabetes-induced chronic hyperglycemia results in the formation and aggregation of advanced glycation end-products (AGEs), which are products of non-enzymatic glycosylation of lipids or proteins. The development of diabetic complications can be accelerated by AGEs. In the current study, we aimed to explore the relationship between AGEs levels and ABC goals of diabetes control (A: Hemoglobin A1C < 7.0%, B: Blood pressure < 140/90 mmHg, and C: low-density lipoprotein cholesterol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…We also found that the concentration of noninvasive lens AGEs was an independent risk factor for the severity of DKD and had a high regression coefficient, which indicates that it has certain clinical value in evaluating the severity of DKD. Rezaei Mohaddeseh et al [ 26 ] found that plasma AGE concentrations were positively correlated with diabetic retinopathy, but no correlation was found between plasma AGE concentrations and DKD. In this study, by measuring the contents of AGEs in the lens, we found that they were correlated with DKD.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that the concentration of noninvasive lens AGEs was an independent risk factor for the severity of DKD and had a high regression coefficient, which indicates that it has certain clinical value in evaluating the severity of DKD. Rezaei Mohaddeseh et al [ 26 ] found that plasma AGE concentrations were positively correlated with diabetic retinopathy, but no correlation was found between plasma AGE concentrations and DKD. In this study, by measuring the contents of AGEs in the lens, we found that they were correlated with DKD.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to an increase in the level of microvascular complications of DM. Rezaei, M. et al support this assumption; their studies show that AGEs measurements are valuable in the follow-up of DM complications, but they were unable to prove a relationship between HbA1c levels and blood sugar regulation and AGE levels in their work [ 26 ]. One reason for the development of MAC may be the accumulation of AGEs in MVA; to confirm this, further tissue analyses are required.…”
Section: Discussionmentioning
confidence: 99%
“…Affecting the nonenzymatic glycation process in the formation of Amadori products, which are initially the basis for the generation and accumulation of advanced glycation products (AGEs) that play an important pathophysiological role in DR, damage to the blood vessels of the retina is caused by the accumulation of AGEs ions within the cells and in the extracellular matrix, which leads to hardening of the blood vessels, which does not allow them to vasodilate and cause them to rupture or become blocked and cause a reduction in blood flow. Additionally, AGEs cause mitochondrial deterioration, and both events cause retinal hypoxia [45].…”
Section: Discussionmentioning
confidence: 99%